(untitled) (INNOVATIVE ECONOMY, 2025)
Patskan V.V. EXPERIENCE OF ANTI-CORRUPTION POLICY IN EU COUNTRIES: LEGAL ANALYSIS AND PROSPECTS FOR UKRAINE Purpose. The aim of the article is to research and analysis of anti-corruption practices of the European Union to identify effective mechanisms and prospects for their adaptation to Ukrainian realities in the context of European integration processes. Methodology of research. The research is based on an integrated approach to the analysis of the anti-corruption policy of the European Union and its impact on the development of anti-corruption measures in Ukraine. The system method is applied to consider the anti-corruption policy of the EU as a whole system of interconnected elements. The comparative legal method was used to compare the anti-corruption norms of the EU and Ukraine, to identify common features and differences. The historical method made it possible to follow the evolution of the anti-corruption policy of the EU and Ukraine. Findings. The article analyses the EU anti-corruption policy and its impact on the development of anti-corruption measures in Ukraine. The key aspects of European anti-corruption practice, in particular, EU legal instruments in the field of anti-corruption, and their reflection in Ukrainian legislation and institutional structure are considered. Attention is focused on the relationship between EU anti-corruption initiatives and reforms in Ukraine, as well as the importance of this interaction for European integration processes and the improvement of anti-corruption policies of both parties. Originality. The article studies the latest EU legislation in the field of anti-corruption policy and its potential impact on the development of anti-corruption measures in Ukraine. Practical value. The obtained results of the study and the proposals developed can be used for further research and may be used to harmonise Ukrainian legislation with European standards and improve the effectiveness of anti-corruption bodies in the context of European integration processes. Key words: anti-corruption policy, European Union, European integration, reforms, anti-corruption.